Marketing Strategy Analysis Of Seri Kuala Lobam Fashion Center Sme: An Stp And Business Model Canvas Approach - Renniwaty Siringoringo; Cosmas Eko Suharyanto; Heryenzus; Suali; Jonmaianto Sihombing (CV Edujavare Publishing, 2026)
Abstract The Seri Kuala Lobam Fashion Centre SME is a strategic initiative established by the Bintan Regency Government to integrate 72 garment manufacturing small and medium-sized enterprises (SMEs) into a collaborative production cluster utilizing computerized embroidery and digital printing technology. This study aims to formulate and analyze a comprehensive marketing strategy by integrating the Segmenting, Targeting, Positioning (STP) framework with the Business Model Canvas (BMC) to develop a holistic business model architecture. A qualitative descriptive-analytical approach was employed using primary data collected through field observations, focus group discussions, and a survey involving 60 business-to-business (B2B) institutional respondents in the Batam–Bintan–Karimun region, complemented by secondary data obtained from the Central Statistics Agency and relevant institutional documents. The findings reveal that the manufacturing and shipbuilding industries constitute the primary target markets, with potential annual demand for workwear (wearpacks) exceeding 20,000 units, while the government and education sectors provide additional opportunities for large-scale production. SWOT analysis indicates a significant gap between existing production capacity and market demand, alongside dependence on externally sourced raw materials as a key structural weakness. Furthermore, the Business Model Canvas demonstrates that the Center’s competitive advantage is built upon three core value propositions: production precision through advanced technology, logistical cost efficiency resulting from its strategic location near industrial estates, and its contribution to local economic empowerment. Nevertheless, improvements in cost structure management and customer relationship development remain essential to achieve long-term business sustainability. The study concludes that integrating the STP and BMC frameworks provides a complementary strategic approach, with STP defining market direction and BMC translating these strategic decisions into an actionable business model. This research offers a novel contribution by presenting the first integrated application of the STP and Business Model Canvas frameworks for developing marketing strategies for SMEs in the Riau Islands.